Diámetro de la aorta abdominal como índice de la normalidad en pacientes sin riesgo cardiovascular atendidos en el Hospital de Especialidades de las Fuerzas Armadas N° 1 de Quito. - lvarez Loaiza, Jhojanna Patricia. (2014)
A descriptive research match was made to determine the normal diameter of the infra renal abdominal aorta in patients without cardiovascular risk factor, treated at the Fuerzas Armadas N°1 Specialties Hospital in Quito. It was made the tomographic measure of the transverse diameter of the infra renal abdominal aorta and transverse diameter of the third lumbar vertebra on 146 patients without cardiovascular risk factors, obtaining the relationship between these measuring in order to compare with the constant of 0.4, relating, moreover, the infra renal aorta diameter with the sex, age, weight, and height variables reflected in the Corporal mass index. The 146 patients showed a normal rank into the relationship between the infra renal aorta and L3 diameters, with quantities from 0.40 to 0.20 down that are similar to the quantities found in foreign population no bigger than 0.40. The average of the infra renal aorta diameter taken in the patients studied is about 1.5 cm oscillating its measure between 1 cm and 2.1 cm, being these quantities alike to the North America population that vary between 1.5 and 2.3 cm. The normal measure of the infra renal aorta is not affected neither the weight nor the height of the patients. KEY WORDS The third lumbar vertebra diameter.